Argentina : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper describes economic developments in Argentina during the 1990s. Since the implementation of the Convertibility Plan in early 1991, real GDP grew by more than 7 percent a year (or by a cumulative 35 percent over the years 1991-94), after stagnating for more than a decade. At the same time, consumer price inflation, which had peaked at 3,000 percent in 1989, declined to 4 percent (average) in 1994. Gross fixed investment recovered to nearly 20 percent of GDP by 1994, reflecting a real growth rate of 22 percent a year during the period.